Mapping Good Work: The Quality of Working Life Across the Occupational Structure - Mark Williams; Ying Zhou; Min Zou (Bristol University Press, 2020)
In this illuminating study of working life, leading experts in the sociology of work draw on decades of large-scale survey data to consider various notions of the quality of work in the Britain. Exploring data on hundreds of occupations, it charts why some occupations feel more rewarding than others and sets out fresh policies that might generate greater fulfilment at work.
Keywords: 330; job quality; job satisfaction; occupations; social statistics; sociology of work